(untitled) (Kathmandu University Medical Journal, 2022)
Background Urinary tract infection (UTI) is common in pregnancy and poses a great challenge because it has several adverse outcomes in both the mother and her unborn foetus. Objective This study aims to determine the incidence of culture positive urinary tract infection, culture and sensitivity of the common causative organisms and find out the maternal and perinatal outcomes in culture positive urinary tract infection. Method This prospective study was carried out in the Department of Obstetrics and Gynaecology at Dhulikhel Hospital over a period of one year. Urine routine and microscopy was done as a preliminary screening test for urinary tract infection and those with abnormal results were subjected to urine culture and sensitivity and ultrasonological evaluation. Result A total of 162 pregnant women were included in the study. Incidence of culture positive urinary tract infection was 25.9%, highest in age group 15-20 years (47.8%), more in primigravida (30.1%) and common at second trimester (40.4%). Escherichia coli (90.4%) was the commonest organism isolated and ceftriaxone was the most sensitive antibiotic. Patients with culture positive urinary tract infection had higher incidence of anaemia, preterm labour, need of surgical intervention. Such patients also had increased chances of preterm delivery, low birth weight babies and newborn intensive care unit (NICU) admission. Conclusion We conclude that urinary tract infection in pregnancy leads to adverse maternal and fetal outcomes. And we recommend urine culture and sensitivity at each trimester so that urinary tract infection can be diagnosed and treated on time.